Pengenalan NAS (Network Attached Storage) untuk Penyimpanan Data Terpusat pada Paguyuban Kebon Manggis - Ika Mei Lina; Gilang Ryan Fernandes (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Paguyuban is an organization of togetherness in a particular social group. This paguyuban is a family welfare coach that strives not only to educate residents, but also to foster and build families in the mental, spiritual and physical material fields as well as improving the quality of food, clothing, shelter, health, and the environment. Paguyuban Kebon Manggis has so far had difficulty in filing data. Along with the development of the paguyuban kebon mangosteen, the amount of data produced by the paguyuban has also increased. This has an impact on the need for data storage. Therefore, the community service proposal team considered it necessary to provide an understanding of the use of NAS (Network Attached Storage) to make it easier for paguyuban members to manage the increasing data. NAS (Network Attached Storage) servers are built to serve the needs of data files that can be accessed via a local area network with the TCP/IP protocol. This activity was carried out in front of the members of Paguyuban Kebon Manggis which was designed in 2 sessions. The first material was the socialization of the introduction of NAS and the second material was about the implementation of the use of NAS (Network Attached Storage). This PKM activity uses presentation methods, application simulations, and direct practice for participants assisted by the team. Then to make it easier, examples are given and opportunities for questions and answers are opened for PKM participants.